2014
DOI: 10.1055/s-0034-1396696
|View full text |Cite
|
Sign up to set email alerts
|

Time from Uterine Incision to Delivery and Hypoxic Neonatal Outcomes

Abstract: Overall, duration from uterine incision to delivery for in-labor cesareans of nonanomalous term infants was not associated with an increase in risk of hypoxia-associated morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…[8][9][10] A shorter U-D interval is desirable, since it is associated with improved maternal and fetal outcomes and fewer complications. [12,13] The findings of this study refute an older study and one case report that suggested that vacuumassisted caesarean section results in longer times to delivery. [5,14] The secondary aim was to examine whether there were differences in perioperative complications in the mother and fetus when comparing the CaesAid VAD cup with forceps.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…[8][9][10] A shorter U-D interval is desirable, since it is associated with improved maternal and fetal outcomes and fewer complications. [12,13] The findings of this study refute an older study and one case report that suggested that vacuumassisted caesarean section results in longer times to delivery. [5,14] The secondary aim was to examine whether there were differences in perioperative complications in the mother and fetus when comparing the CaesAid VAD cup with forceps.…”
Section: Discussioncontrasting
confidence: 64%
“…Increased time to delivery of the fetal head is associated with compromised maternal and fetal outcomes and more complications. [12,13] The secondary objective was to assess whether there was a difference in perioperative complications in the mother and fetus between the two methods of delivery.…”
mentioning
confidence: 99%
“…7 In addition, higher order cesarean delivery is associated with an increased operative time. 6,10,13,14 While evidence is mixed regarding neonatal effects of prolonged operative time, a longer incision to delivery interval has been associated with an increased frequency of neonatal hypoxic morbidity. 1415 An unscheduled presentation due to labor only serves to compound these risks.…”
mentioning
confidence: 99%
“…According to the literature, there does not appear to be any significant difference in hypoxic morbidity with increasing increments of the uterine incision to delivery time of non-anomalous term neonates. 14 For the non-reassuring fetal status, if the delivery time of the fetal head exceeds 240 s, the incidence of neonatal asphyxia significantly increases (relative risk, 5.58; 95% confidence interval: 1.30–23.91). 15 In clinical practice, delivering the fetus within 3 minutes is difficult, especially for a fetus with a head deep in the pelvis, which is more challenging for inexperienced physicians.…”
Section: Discussionmentioning
confidence: 99%